Experience in prenatal ultrasound diagnosis of fetal microtia and associated abnormalities - Qiu, Jing; Ru, Yanhui; Gao, Yang; Shen, Jie (Frontiers in Medicine, 2023)
Objective Prenatal ultrasound features, associated anomalies and genetic abnormalities of microtia cases were analyzed to explore the feasibility and value of prenatal ultrasound for the diagnosis of microtia. Methods The ultrasonographic features, associated anomalies, chromosome examination results and follow-up results of 81 fetuses with congenital microtia were analyzed retrospectively. Results Among the 81 fetuses with microtia diagnosed after birth, 2 cases were missed diagnosis on prenatal ultrasound, and 1 case was diagnosed as unilateral microtia by prenatal ultrasound but was found to be bilateral microtia after birth. Microtia was accompanied by an accessory auricle in 4 cases (4.94%) and low-set ears in 7 cases (8.64%). 22 cases (27.16%) were complicated with other structural anomalies, including 11 cases (13.58%) of cardiac anomalies, 7 cases (8.64%) of ultrasonographic soft marker anomalies, 6 cases (7.41%) of facial anomalies, 6 cases (7.41%) of nervous system anomalies, 3 cases (3.70%) of urogenital system anomalies, 3 cases (3.70%) of digestive tract anomalies and 2 cases (2.47%) of limb anomalies. Chromosome karyotype analysis and gene detection were performed in 44 cases. Trisomy 18, trisomy 13, trisomy 21, pericentric inversion of chromosome 9, partial loss of heterozygosity on chromosome 14, 22q11 microdeletion and a normal karyotype were found in 2 cases, 2 cases, 3 cases, 1 case, 1 case, 1 case, and 34 cases, respectively. Conclusion In summary, microtia is often accompanied by congenital defects of other organs and structures, especially the heart and face, and prenatal ultrasound diagnosis of microtia and associated anomalies is of important clinical significance.